The Relationship Between Self-Concept and Assertive Behavior of Students - Kusumawati Kusumawati; Rakhmawati Rakhmawati; Hartini Hartini (Indonesian Journal Of Educational Research and Review, 2021)
Adolescents are required to be open and firm in expressing their opinions and thoughts to others without losing their self-confidence. However, the data shows that 3.69% still behave and speak dishonestly, 2.30% of students find it challenging to communicate. The purpose of this study is to analyze the relationship between self-concept and student assertive behavior. This study uses a quantitative ex post facto method. The total population used is 101 students. The instrument used in this research is the self-concept scale and the students' assertive behavior scale. The reliability analysis using Cronbach's Alpha formula was obtained from the assertive behavior scale of 0.864, the self-concept scale of 0.894. This figure is then consulted with the product-moment table for N=34, with a 5% significance level of 0.339. The value of the coefficient of determination R2 generated is 0.284, which means that 28.4% of assertive behavior is influenced by self-concept, while the remaining 71.6% can be influenced by other variables not examined. BK teachers should provide guidance and counseling services according to the needs of students. Students who have a high category should be given individual counseling immediately. According to the needs of students at that time.